TRANSFORMATION OF CHARACTER EDUCATION IN ARABIC LANGUAGE EDUCATION THROUGH A COMMUNICATIVE APPROACH AT SMAI BAWARI PONTIANAK - Ega Ulandari; Wahab Wahab; Eka Hendry Ar (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
Character education is important in life to build students' personalities. The purpose of this research is to explain the ethical and moral principles that influence a person's feelings and actions. The method used is a qualitative research method with a communicative approach. Data were collected through interviews and classroom observations at SMAI Bawari Pontianak. The results of the study showed that the use of communication increased students' motivation in learning Arabic and improved their ability to understand vocabulary and sentence structure. This study concludes that communicating in language learning can improve the quality of learning in the digital era. The application of a communicative approach has implications for students to be actively involved in relevant interactions, not only learning language, but also moral values and positive characters that can be applied in everyday life. The final results of this study indicate that the integration between character education and Arabic language learning is very important in today's global context, where language mastery and character formation are interrelated and insepara.